Resilient Women of Sidoarjo Self-Efficacy, Innovation, and Determination in Improving Culinary Business Performance - Eka Robi'atul Al Adawiyah; Vera Firdaus; Sumartik Sumartik (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines women's resilience in Sidoarjo, with an emphasis on self-efficacy, innovation, and perseverance in the culinary sector. These factors are crucial because they boost confidence, create competitive advantages, and help overcome local economic challenges. Methodology: Using a Quantitative Causal Research, this study utilizes cluster sampling for data collection in several subdistricts of Sidoarjo Regency in 2025, involving 105 representative respondents. This study uses validity, reliability, and classical assumption tests, as well as out-of-model testing, convergent validity, average variance extracted (AVE), composite reliability, Cronbach's alpha, and r-squared. Results: Findings indicate that self-efficacy (T = 3.174, P = 0.002), innovation (T = 2.034, P = 0.042), and perseverance (T = 2.647, P = 0.008) have a positive effect on culinary business performance. These results underscore the importance of psychological factors and strategic approaches for the success of female entrepreneurs in the culinary field. Findings: self-efficacy, innovation, and determination on culinary business performance in Sidoarjo Regency, it can be concluded that these three variables have a positive and significant effect on culinary business performance. Novelty: The novelty of this study lies in its focus on female culinary entrepreneurs in Sidoarjo using SmartPLS-based analysis. Originality: This study stands out for examining self-efficacy, innovation, and perseverance in relation to women's business performance.. Conclusion: Women's self-confidence has a significant impact on performance, followed by innovation in product development and determination with a small positive impact. It is necessary to increase courage for economic independence. Type of Paper: This paper is an empirical research paper.